Physiology of retinal reattachment in humans: Swept source optical coherence tomography imaging data supporting a novel staging system - Aditya Bansal (Elsevier, 2021)
This article presents high-resolution swept source optical coherence tomography (SS-OCT) imaging data used to describe the physiology of retinal reattachment in humans. SS-OCT imaging was performed at baseline and every 2 h for the first 6 h and at frequent intervals thereafter up to 6 weeks following the injection of intravitreal gas in eyes undergoing pneumatic retinopexy for rhegmatogenous retinal detachment. Imaging data presented in this article is related to the research paper titled “Real-Time in Vivo Assessment of Retinal Reattachment in Humans using Swept-Source Optical Coherence Tomography” (Bansal et al., 2021). SS-OCT images were assessed longitudinally and used to devise a novel staging system that describes the physiology of retinal reattachment. Multiple examples of each stage and the transition from one stage to the next are provided. SS-OCT images were also assessed to determine the timing associated with each stage, and the anatomic abnormalities, such as outer retinal folds and subretinal fluid blebs that occured as a result of delayed progression through certain stages.